ANALISA SISTEM EMISI GAS BUANG PADA ENGINE TRAINER SUZUKI CARRY ST 100 - , LAMBOK RAYMOND, Ir. Susanto Johanes, MT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nowadays, the transportation is the best solution was made for people went to a place easily. Especially car mostly used to far location and owner was made comfortable with the jorney. But, most of people didnât knew about the exhaust gas emissions from the car is dangerous for our healthy. The exhaust gas emissions was made residue of combustion from the car. The contents of exhaust gas emissions is CO, NOx, and HC. Finally, exhaust gas emissions were analyzed and made for the final project report. This final project report is the result of research about exhaust gas emissions came out from muffler. The type of car used in the research was Suzuki Carry ST 100. The writer is testing exhaust gas emissions used PROTECH FLUX 5000 infrared gas analyzer with speed variety of 1000, 1500, and 2000 rpm. From the results of testing exhaust gas emissions from PROTECH FLUX printed out on 1000 rpm is CO 0,22 %, CO2 0,585 %, O2 5,42 %, HC 296 ppm. And then, on 1500 rpm is CO 6,86 %, CO2 8,43 %, O2 2,93 %, HC 850 ppm. And the last on 2000 rpm is CO 7,6 %, CO2 9,965 %, O2 3,84 %, HC 841 ppm. From the research, it can be concluded that the engine trainer Suzuki Carry ST 100 was made has good emission and save environment because the results of CO, CO2, O2, and HC is lower than the standardization.